HUBUNGAN KARAKTERISTIK IBU (USIA DAN PARITAS) DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) DI RSUD S.K. LERIK KOTA KUPANG - MARIA ERVIN HARTINA MUU; Florentianus Tat; Maria Paula Marla Nahak (STIKes CHMK, 2022)
Low birth weight (LBW) is one of the causes of infant mortality in Indonesia. The incidence of low birth weight babies (LBW) accounts for 38.85% of the infant mortality rate in Indonesia. Birth weight is an important indicator related to vulnerability to disease risk and child survival. Objective: This study aims to determine the relationship between maternal characteristics (age and parity) with the incidence of low birth weight (LBW) in RSUD SK Lerik, Kupang City. This type of research is observational analytics with a case control study approach with the number of samples is 74. Sampling techniques using consecutive sampling and analyzed using chi square test. Results and Discussion: The relationship of maternal age with the incidence of LBW obtained ρ-value = 0,259 (α < 0,005), while the relationship of maternal parity with the incidence of LBW obtained the value of the ρ-value = 0,809 (α < 0,005). Conclusions and Recommendations: There is no relationship between maternal age and parity with the incidence of LBW at RSUD S. K Lerik, Kota Kupang. Suggestions for health workers to improve effective communication, information and education services about safe age and parity for mothers to give birth to prevent the incidence of LBW Keywords: Maternal age, Parity, LBW